Examining AIS Software and Co-operative Performance in Malaysia - Harun Rasit, Mohd Hadzrami; Ibrahim, Mohammad Azhar (OMJP Alpha Publishing, 2017)
Accounting information systems (AIS) is essential to process business data into useful information. Indeed, empirical evidence suggested that the use of AIS has a positive impact on firm performance.Previous studies were concentrating on small and medium-sized enterprises (SMEs) and public listed companies leaving a gap in the co-operative literature.Furthermore, the users of different types of AIS software that contribute towards improving the firm performance were not adequately explored.As such, this paper draws on the resource-based view (RBV) to examine the gap issue.Using mail questionnaire survey, data were collected from 120 co-operatives. Findings from this study suggest that commercial and developed-inhouse AIS software are mostly used by co-operatives.Also, the findings suggest that co-operatives performance is not associated with the types of AIS software used by the cooperatives.This study provides valuable insights into the implementation of AIS among Malaysian co-operatives, which has received little attention thus far from academic, governmental and professional bodies.